Sanctions for Recidivist Drug Offenders From the Perspective of Penitentiary Law - Iwan Rasiwan; Rundasih Rundasih (INFOKUM, 2025)
This study examines the effectiveness of penal sanctions for recidivist drug offenders in Indonesia from the perspective of penitentiary law. The findings reveal that Indonesia’s punitive approach, characterized by severe incarceration measures, has failed to reduce recidivism rates, which remain among the highest globally. Comparative analysis with jurisdictions such as Norway, Portugal, and the Netherlands demonstrates that rehabilitation-based justice models, incorporating structured treatment programs and alternative sentencing, have yielded significantly lower recidivism rates. The study identifies key challenges within Indonesia’s criminal justice system, including prison overcrowding, lack of access to rehabilitation programs, and post-incarceration social exclusion, all of which contribute to the cycle of reoffending. The research suggests that a shift toward evidence-based rehabilitative measures, including diversion programs, proportional sentencing, and community-based reintegration efforts, is crucial for improving Indonesia’s approach to drug-related recidivism. By aligning its legal framework with international best practices, Indonesia can develop a more effective and sustainable criminal justice strategy that prioritizes rehabilitation over punitive incarceration.